Neurogenic Processes Are Induced by Very Short Periods of Voluntary Wheel-Running in Male Mice - Gremmelspacher, Teresa; Gerlach, Johannes; Hubbe, Alix; Haas, Carola A.; Häussler, Ute (Frontiers in Neuroscience, 2017)
Even in the adult mammalian brain progenitor cells proliferate and give rise to young neurons which integrate into the neuronal network. The dentate gyrus possesses such a neurogenic niche reactive to external stimuli like physical activity. In most studies mice or rats have been exposed to wheel running for periods of several weeks to activate neurogenesis while early neurogenic processes induced by very short running periods are less well understood. To address this issue, we allowed male C57Bl/6 mice free access to a running wheel for two or seven days. We injected bromodeoxyuridine (BrdU) before the last running night, respectively, and quantified cell proliferation with immunocytochemistry for BrdU and Ki-67. Furthermore, we performed immunocytochemistry for doublecortin (DCX) and real-time RT-qPCR for NeuroD1 to characterize and quantify changes in neurogenesis on the protein and mRNA level. Real-time RT-qPCR for neurogenic niche factors (BDNF, FGF-2, BMP4, Noggin) was used to detect changes in the molecular composition of the neurogenic niche. Interestingly, we observed that cell proliferation was already affected after two days of running showing a transient decrease, which was followed by a rebound with increased proliferation after seven days. Neurogenesis was stimulated after two days of running, reflected by elevated NeuroD1mRNA levels, and it was significantly increased after seven days as indicated by DCX immunostaining. On the level of niche factors we observed changes in expression in favor of neuronal differentiation (increased BDNF mRNA expression) and proliferation (decreased BMP4 mRNA expression) already after two days, although increased proliferation is reflected on the cellular level only later. In summary, our data show that two days of running are sufficient to activate neurogenic processes and we hypothesize that a strong pressure towards differentiation privileges neurogenesis while proliferation lags behind.